The Effect of Measurement Alternatives on a Nonfinancial Quality Measure's Forward-Looking Properties - Sedatole, Karen L. (The Accounting Review, 2003)
Drawing on theories from operations, management, and marketing, this paper examines whether three types of measurement alternatives affect the forwardlooking properties of a quality measure. Using proprietary data from a medical services firm, the results show that the strength of the relation between a current quality measure and future quality-related warranty costs depends on: (1) the standard against which quality is measured, (2) assumptions regarding the relation's symmetry, and (3) assumptions regarding the relation's functional form. Thus, the construction of a quality performance measure may improve its ability to predict future financial performance and, hence, its usefulness for decision making and control. The paper concludes with an illustration of how firms can use a contemporaneous and forward-looking quality measure to assess quality-related decisions in a timely manner and shows that those decisions can be affected by the measurement alternatives examined.